Analyzing the evidence of an IPR take-off in China and India - Godinho, Manuel Mira (2012)
Both China and India have been experiencing a historical take-off in the use of intellectual property rights (IPR). In terms oftrademark applications filed with domestic IP offices in 2009,the evidence demonstrates that China now ranks 1st worldwide and India 5th, while for patent filings China ranks 3rd worldwide and India ranks 9th. This performance is remarkable as both China and India experienced negligible demand for IPR protection as recently as two decades ago. The IPR take up trends in these two countries are analyzed in detail, highlighting the structure of patent and trademark demand since 1990. Specifically, the available series are broken down and analyzed according to: (i) national versus foreign origin of patents and trademarks;(ii) technological (IPC) and trademark (NICE) classes; and (iii)the major individual patent users in each country. The data used refers to applications in the Chinese and Indian IP offices although the demand from residents of these two countries in both the international and other national systems is also assessed. Beyond the existing momentum in IPR registrations by China and India and their capacity to maintain it into the near future, the paper addresses practical questions about the strategies, motives and benefits behind the current trends. In particular, we seek to evaluate the capacity of both China’s and India’s National Innovation Systems to internalize the potential returns of this increasing demand for IPR. The insight reached finds that should both China and India sustain their current IPR growth rates, they will be able to catch up with the most advanced economies within the time span of a few decades